197k views
2 votes
What is a correct first step in solving the inequality –4(3 – 5x)≥ –6x + 9?

User SSA
by
4.6k points

2 Answers

1 vote

Answer:

Distributive property.

Explanation:

-4(3-5x) ≥ -6x + 9 (given)

-12 + 20x ≥ -6x + 9 (distribute)

26x ≥ 21 ( addition property of inequality)

x ≥ 1.24 ( division)

User Maga
by
5.9k points
7 votes

Answer:

the first step is to distribute the -4 to (3-5x)

Explanation:

User Olokoo
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.